Design and Performance Analysis of 250 kW Grid-Connected Photovoltaic System in Iraqi Environment Using PVsyst Software - Oday A Ahmed; Waleed H. Habeeb; Dhari Y. Mahmood; Kanaan A Jalal; Hussain K Sayed (IAES Indonesian Section, 2019)
A 250 kW grid-connected photovoltaic (PV) plant systems have been installed at the Ministry of Electricity in Baghdad and penetrated to the Iraqi national grid since November 2017. This is the first high power grid-connected PV system that has been installed in Iraq and it’s one of the four parts 1MW large-scale PV systems that should be completed in early of 2019. This paper presents the design and performance analysis of this system using a PVsyst software package. The performance ratio and different losses that occurred in the system are also calculated. The results show that the performance ratio is 75% using 1428 photovoltaic panels type (Sharp 175Wp) spread over an area of 1858 m². The total energy injected into the grid is (346692 kWh/year) .Based on the simulation results that developed in this paper, the practical PV grid-tied system has been implemented in Baghdad site.